2007
DOI: 10.1177/016264340702200402
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration Strategies Reported by Teachers Providing Assistive Technology Services

Abstract: Collaboration between special educators and general education teachers is associated with academic and social success of students with disabilities who are included in the general education classroom. This study reports the findings from 96 interviews conducted with special and general education teachers regarding collaboration strategies to provide assistive technology services to students. Strategies such as collaborative consultation, problem solving, and teaming are discussed, and interview findings are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In contrast, as a component of more extensive reform efforts and their associated professional development programs, educators may have the opportunity to receive more support from professional development communities, benefit from coaching, and extend their learning about AT across time. Efforts to expand collaboration and coteaching are another reasonable nexus at which to expand expertise about AT (McLaren, Bausch, & Ault, 2007).…”
Section: Educators Need Different Approaches To Preparation Andmentioning
confidence: 99%
“…In contrast, as a component of more extensive reform efforts and their associated professional development programs, educators may have the opportunity to receive more support from professional development communities, benefit from coaching, and extend their learning about AT across time. Efforts to expand collaboration and coteaching are another reasonable nexus at which to expand expertise about AT (McLaren, Bausch, & Ault, 2007).…”
Section: Educators Need Different Approaches To Preparation Andmentioning
confidence: 99%
“…Teachers articulated their concerns about the need for training. Providing training for teachers of students with disabilities may enhance their efforts in planning and implementing technology in their classrooms (McLaren, Bausch and Jones Ault, ). Teachers’ perceptions of the inadequacy of training may be related to their lack of knowledge about the skills needed by students to use technology in classrooms (Smith and Allsopp, ).…”
Section: Discussionmentioning
confidence: 99%
“…They used the term 'collaborative teaming' to refer to the involvement of teachers, instructional assistants and speech and language therapists in the implementation of AAC systems in mainstream school settings. In interviews with teachers, McLaren et al (2007) explored the ways in which teachers worked with other groups of practitioners when using assistive technology in schools. They found that this was dependent on the importance placed by teachers on participation of all parties, meetings, effective communication and collaborative planning.…”
Section: Literaturementioning
confidence: 99%